New Planktonic Foraminifera Data from the Upper Cretaceous Pelagic Limestones of the Yuksekova Complex in the Maden Area (Southeast of Elazig, Eastern Turkey) - Ural, Melek; Sari, Bilal (Institute of Physics Publishing, 2019)
The units situated in Southeast Anatolian Orogenic Belt within the Bitlis-Zagros suture zone, are still controversial. Therefore, it is important to obtain new data from the subduction/accretion complexes along the southeast Anatolian-Zagros suture belt in the Eastern Mediterranean. Hence, this study was carried out to find out whether the pelagic limestones overlying the volcanogenic rocks in the Maden area (southeast of Elazi?) belong to Yüksekova Complex or Maden Complex. The lavas intercalated with pelagic limestones are dark-colored, pillow shaped and massive basalts. They are commonly amygdaloidal structured showing surface cavities filled with secondary minerals. The thick-bedded limestones are mainly represented by rare planktonic foraminifera bearing wackestone and mudstone depositional texture. Rare planktonic foraminifera in the rocks are mainly represented by double keeled marginotruncanids, which are characteristic organisms of the Turonian-Santonian interval of the Late Cretaceous. Poor planktonic foraminifera assemblages obtained from the micritic limestones comprise Marginotruncana aff. marginata and M. cf. paraconcavata. According to these taxa, the age of the volcanogenic formation is Turonian-Santonian. The volcaniclastic sequence discussed in this study, were considered to be part of the Middle Eocene Maden Complex in previous studies. But, the results show that the studied volcaniclastic succession belong to the Yüksekova Complex as the age of the micritic limestones is Late Cretaceous but not Middle Eosen. © Published under licence by IOP Publishing Ltd.
5th World Multidisciplinary Earth Sciences Symposium, WMESS 2019 -- 9 September 2019 through 13 September 2019 -- Prague -- 155452
Keywords: Earth sciences; Lime; Textures; Volcanoes; Depositional texture; Eastern Mediterranean; Late cretaceous; Planktonic foraminifera; Planktonic foraminifera assemblages; Upper Cretaceous; Volcaniclastics; Volcanogenic rocks; Limestone